2017
DOI: 10.1038/s41598-017-00671-1
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 is upregulated, but not essential in hepatic fibrogenesis and carcinogenesis in mice

Abstract: Tissue inhibitor of metalloproteinases-1 (TIMP-1) is upregulated during hepatic fibrogenesis and considered to promote fibrosis in the injured liver by inhibition of matrix metalloproteases (MMP) and degradation of extracellular matrix. Moreover, TIMP-1 displays anti-apoptotic properties, in patients with hepatocellular carcinoma (HCC) TIMP-1 serum levels are elevated and high TIMP-1 expression levels in HCC are associated with a poor prognosis. Therefore, TIMP-1 could functionally link fibrogenesis and carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
(46 reference statements)
0
26
0
2
Order By: Relevance
“…58 TIMPs are well-studied proteins in liver fibrosis, and their expression is in inverse correlation to that in the disease stage. 59 Previous reports suggest that TIMP-1 overexpression inhibits MMPs activity and leads to a decrease in clearance of ECM. 60 The interaction between activated hepatic myofibroblasts and Kupffer cells results in increased TIMP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…58 TIMPs are well-studied proteins in liver fibrosis, and their expression is in inverse correlation to that in the disease stage. 59 Previous reports suggest that TIMP-1 overexpression inhibits MMPs activity and leads to a decrease in clearance of ECM. 60 The interaction between activated hepatic myofibroblasts and Kupffer cells results in increased TIMP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The second profibrogenic protein is TIMP-1, which prevents dissolving or dissociation of the ECM via the inhibition of matrix metalloproteinases and hence promote fibrosis (Yoshiji et al, 2000). However, a recent report (Thiele et al, 2017) demonstrated only association and not the promotion of liver fibrosis by TIMP-1. HIF-1α and mTOR were found to increase these profibrogenic biomarkers and hence promote fibrosis (Hu et al, 2017;Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Type IV collagenases are implicated in tumor cell invasion and migration processes (22,23). MMPs are controlled by endogenous tissue specific inhibitors, also known as tissue inhibitors of metalloproteinases (TIMPs) (24). TIMP1 can inhibit tumor progression by suppressing MMP9-mediated release of vascular endothelial growth factor from the matrix.…”
Section: Discussionmentioning
confidence: 99%